Determinants of Climate Change Awareness among Rural Farming Households in South Africa - Samuel, Oduniyi Oluwaseun; Micheal, Antwi; Nkonki-Mandleni, Busisiwe (Journal of Economics and Behavioral Studies, 2018)
Climate change and rural livelihood capitals remain the major inextricable dimensions of sustainability in this twenty-first century globally. It is known to be an important challenge facing food security status among African countries. Additionally, it is an indisputable fact that climate change and agriculture are intertwined. In view of this, climate change awareness needs to be strengthened in the rural farming households. The study was carried out in Ngaka Modiri Molema District Municipality, in the North West Province of South Africa to determine awareness of climate change. Stratified random sampling technique was used to select three hundred and forty-six (346) farmers who were interviewed from the study area. Data were analyzed using statistical package for social sciences (SPSS). The binary logistic regression model was employed to analyse the factors driving climate change awareness. The study established that majority of the rural farmers in the study area aware of climate change, in which farm size, education, who owns the farm, information received on climate change, source of climate change information, climate change information through extension services, channel of information received on climate change and support received on climate change are statistically significant (p<0.05) determinants of climate change awareness in the study area.